P–215 The degree of perivitelline space (PS) at the pronuclear stage affects subsequent embryonic development in human zygotes. (6th August 2021) - Yumoto, K; Shimura, T; Sugishima, M; Nakaoka, M; Mio, Y
Abstract: Study question: Was embryonic development affected by the degree of perivitelline space (PS) at the pronuclear stage in human zygotes? Summary answer: Zygotes with a fully surrounding PS showed less cytoplasmic fragmentation and a higher blastocyst development rate (BDR) than zygotes with a partially surrounding PS. What is known already: We previously used abnormally-fertilized oocytes (zygotes with three pronuclei; 3PN), donated by ART patients in our clinic who gave written consent for the research. The zona pellucida (ZP) was artificially removed from these oocytes at the pronuclear stage, termed ZP-free culture. The resultant ZP-free 3PN embryos showed less cytoplasmic fragmentation and a higher rate of good-quality embryos (GQE) compared with ZP-intact embryos. Furthermore, in our clinical setting, the rate of GQE and BDR of normally-fertilized embryos were clearly improved by ZP-free culture in patients with recurrent failure of ART treatments due to severe cytoplasmic fragmentation at the early cleavage stage. Study design, size, duration: This study included 49 patients who gave written informed consent for our study and were treated with ART in our clinic between March and December 2020. Embryonic development was compared between zygotes with a fully surrounding PS [PS(+)] with those with a partially surrounding PS [PS(-)] at the pronuclear stage. Furthermore, the ZP of PS(-) embryos were artificially removed at the pronuclear stage, and the rate of GQE and BDR were compared with ZP-intact embryos. Participants/materials, setting, methods: The degree of PS in 128 zygotes was confirmed by hypertonic preparation using 0.125M sucrose-containing HEPES medium. PS(+) and PS(-) embryos were both cultured as ZP-intact, and the rate of GQE was compared. Furthermore, 223 zygotes were divided into three groups: 1) PS(-)/ZP-intact, 2) PS(-)/ZP-free, and 3) PS(+)/ZP-intact, and cultured in an incubator equipped with time-lapse monitoring up to Day 7, and the rate of GQE, BDR and useable embryos were compared between each groups. Main results and the role of chance: The degree of PS was confirmed by a hypertonic preparation (shrinkage of the ooplasm) in 128 normally-fertilized zygotes obtained from 44 cases. There were 86 PS(-) (67.2%) and 42 PS(+) (32.8%) zygotes. The mean maternal age was 35.9 in PS(-) and 40.5 in PS(+) (P < 0.01), and the rate of GQE was significantly higher in PS(+) [64.3% (27/42)] than in PS(-)[38.4% (33/86)] (P < 0.01). In addition, of 223 normally-fertilized zygotes obtained from 41 cases, there were 51 PS(-)/ZP-intact (Group 1), 132 PS(-)/ZP-free (Group 2) and 40 PS(+)/ZP-intact (Group 3) zygotes. The rate of GQE was significantly lower in Group 1 [29.4% (15/51)] compared with Group 2 [59.8% (79/132)] and Group 3 [62.5% (25/40)] (P < 0.01). BDR was also significantly lower in Group 1 [51.3% (10/39)] compared with Group 2 [75.0% (99/132)] and Group 3 [65.0% (13/20) (P < 0.01). Limitations, reasons for caution: Although the artificial removal of ZP at the pronuclear stage (ZP-free culture) clearly increased the rate of GQE, embryonic development was not improved in all cases. It seems that this procedure is only effective in embryos with a viable ooplasm. Wider implications of the findings: The degree of PS at the pronuclear stage affects subsequent embryonic development in human zygotes. The artificial removal of ZP at the pronuclear stage (ZP-free culture) helps to suppress fragmentation and leads to an increase in GQE and BDR, and eventually, improves pregnancy rate in cases with severe fragmentation. Trial registration number: non